Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-13T17:23:45+01:00
W każdym przykłądzie najpierw redukujemy wyrazy podobne:
a) 3x-2-2x+5+4x ; gdy x = 12
3x-2x+4x -2+5= 5x +3
5*(12) + 3 = 60 +3 = 63

b) 3a-b+5a+2b-6 ; gdy a= 2 i b= 2
3a+5a -b+2b -6=8a +b - 6
8*(2) +1*(2) - 6= 16 + 2 - 6 = 12

c) x+2y-3y-3z+5z-x ; gdy x= 5 y= 8 z= 6
x-x +2y-3y -3z+5z = -y + 2z
-1*(8) + 2*(6) = -8+12=4

d) 3(x-4z+y+4x-z+2y) ; gdy x=1 y= 2 z=12
3(x+4x +y+2y -4z-z) = 3(5x + 3y - 5z) = 15x + 9y - 15z
15*(1) + 9*(2) - 15*(12) = 15+18-180=-147
2010-01-13T17:24:29+01:00
A) 3x-2-2x+5+4x ; gdy x = 12
b) 3a-b+5a+2b-6 ; gdy a= 2 i b= 2
c) x+2y-3y-3z+5z-x ; gdy x= 5 y= 8 z= 6
d) 3(x-4z+y+4x-z+2y) ; gdy x=1 y= 2 z=12

a)
3*12-2-2*12+5+4*12 = 36 - 2 - 24 + 5 + 48 = 63

b)
3*2 - 2 +5*2+2*2-6 = 6 - 2 + 10 + 4 - 6 = 12

c)
5+2*8-3*8-3*6+5*6-5 = 5 + 16 - 24 - 18 + 30 - 5 =4

d)
3(x-4z+y+4x-z+2y) = 3x - 12z + 3y + 12x - 3z + 6y = 3*1 - 12*12 + 3*2 + 12*1 - 3*12 + 6*2 = 3 - 144 + 6 + 12 - 36 + 12 = - 147
1 5 1